2013
DOI: 10.1242/jeb.087569
|View full text |Cite
|
Sign up to set email alerts
|

Compensations for increased rotational inertia during human cutting turns

Abstract: Locomotion in a complex environment is often not steady state, but unsteady locomotion (stability and maneuverability) is not well understood. We investigated the strategies used by humans to perform sidestep cutting turns when running. Previous studies have argued that because humans have small yaw rotational moments of inertia relative to body mass, deceleratory forces in the initial velocity direction that occur during the turning step, or 'braking' forces, could function to prevent body over-rotation durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…68) states that directional changes must be planned and initiated in the step before the turn to facilitate effective COD performance. This is substantiated by previous studies that have reported athletes make anticipatory postural adjustments (APA) in the step prior to (penultimate foot contact (PFC)) the COD (final foot contact (FFC)), demonstrating kinematic changes in foot placement, trunk lean and rotation, and head rotation (37,51,60,69,93,95). Furthermore, braking characteristics such as greater braking forces and external knee flexor moments (KFM) have been reported in the step prior (PFC) to CODs ≥ 60˚ (20,25,(42)(43)(44)(45), highlighting the importance of the PFC during extreme directional changes.…”
Section: P a G E |supporting
confidence: 69%
“…68) states that directional changes must be planned and initiated in the step before the turn to facilitate effective COD performance. This is substantiated by previous studies that have reported athletes make anticipatory postural adjustments (APA) in the step prior to (penultimate foot contact (PFC)) the COD (final foot contact (FFC)), demonstrating kinematic changes in foot placement, trunk lean and rotation, and head rotation (37,51,60,69,93,95). Furthermore, braking characteristics such as greater braking forces and external knee flexor moments (KFM) have been reported in the step prior (PFC) to CODs ≥ 60˚ (20,25,(42)(43)(44)(45), highlighting the importance of the PFC during extreme directional changes.…”
Section: P a G E |supporting
confidence: 69%
“…Though subsystem momentum and initial stance configuration were previously studied in pirouettes with increased rotational demand (Imura & Yeadon, 2010;Kim et al, 2014;Sugano & Laws, 2002), the role of each leg towards linear and angular impulse generation has not been identified, despite its implications to help dance training. In a cutting maneuver with increased rotational demands, as moment of inertia about a vertical axis increased, the horizontal reaction force (RFh) did not change direction relative to the support leg and the RFh magnitude perpendicular to the CM advancement direction generally increased when the phase duration was similar (Qiao, Brown, & Jindrich, 2014). Additionally, in the golf swing, increases in rotation requirements were satisfied by increasing the magnitude of the RFh at one or both legs (McNitt-Gray et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Stability can be achieved via passive “self-correction” mechanisms or through active generation of corrective forces [ 1 , 2 ]. As passive stability increases, larger impulses will be required to overcome the body’s resistance to movement [ 3 , 4 ]. Highly stable locomotion patterns that position one’s body to passively resist external perturbations can limit maneuverability, because the body will indiscriminately resist any self-imposed forces intended to change one’s trajectory [ 5 ].…”
Section: Introductionmentioning
confidence: 99%